Building capacity in AAC: A person-centred approach to supporting participation by people with complex communication needs. (2nd January 2019) - McNaughton, David; Light, Janice; Beukelman, David R.; Klein, Chris; Nieder, Dana; Nazareth, Godfrey
Abstract: Effective communication is based both on the capacity of the person with complex communication needs, and of other key stakeholders (including communication and education professionals, family members, community partners, and healthcare professionals), to ensure that appropriate AAC supports are provided. In this paper, we describe strategies to build awareness of AAC and to assist people with complex communication needs in obtaining needed services; to build the knowledge, skills, and attitudes of AAC service providers; to provide instruction for people with complex communication needs, as well as communication partners and advocates; and to develop communication supports in society more broadly. We also provide an agenda for building capacity in research and development activities to support full participation by people with complex communication needs throughout society.